2020
DOI: 10.1136/bmjgh-2020-002705
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural insights to support increased consumption of quality protein maize by young children: a cluster randomised trial in Ethiopia

Abstract: IntroductionBiofortified crops have tremendous potential to improve child nutrition. We tested whether complementing the distribution of quality protein maize (QPM) with a package of interventions informed by behavioural insights could support greater consumption of QPM by young children and translate into improved growth.MethodsWe conducted a cluster-randomised trial in Oromia, Ethiopia. Clusters of households with a child between 6 and 35 months were randomised into an arm receiving QPM seed only (320 househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…In addition, our results contribute to the growing literature that demonstrates the utility of using nudging interventions to influence people's food choices (Bucher et al, 2016;Hollands et al, 2017;Lehner et al, 2015;Lycett et al, 2017). Our results are also consistent with the findings that knowledge about the social norms with regard to a new technology affects people's behaviour and that this, in turn, affects the decision to adopt the new technology (Bandiera and Rasul, 2006;BenYishay and Mobarak, 2019;Donato et al, 2020;Krishnan and Patnam, 2014).…”
Section: 5-discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, our results contribute to the growing literature that demonstrates the utility of using nudging interventions to influence people's food choices (Bucher et al, 2016;Hollands et al, 2017;Lehner et al, 2015;Lycett et al, 2017). Our results are also consistent with the findings that knowledge about the social norms with regard to a new technology affects people's behaviour and that this, in turn, affects the decision to adopt the new technology (Bandiera and Rasul, 2006;BenYishay and Mobarak, 2019;Donato et al, 2020;Krishnan and Patnam, 2014).…”
Section: 5-discussionsupporting
confidence: 89%
“…The effects of the treatments on farmers' wtp for biofortified yellow maize seed can be The effect is significant and consistent with a recent study conducted in Ethiopia, which showed a positive effect of nutrition messaging in changing consumption behaviours (Donato et al, 2020). The result is also consistent with a study conducted in Kenya and Uganda that also showed that availing nutrition information increases consumers' wtp for improved porridge flour (Chege et al, 2019).…”
Section: Treatment Effectssupporting
confidence: 88%
See 2 more Smart Citations
“…Full-text eligibility checks of the remaining 52 articles excluded 29 studies. The reasons for exclusion of studies included: 4 studies were duplicates, [42][43][44] 1 study was cross-sectional, 45 2 studies used qualitative evaluation, 46 47 10 studies were abstracts, [48][49][50][51][52][53][54][55][56][57] 4 studies were based on the design and implementation of interventions, [58][59][60][61] 5 studies did not measure IYCF outcomes, [62][63][64][65][66][67][68][69][70] and 3 studies were based on interventions designed for different target groups [71][72][73] (figure 1). Among the 23 included studies, 14 were quasiexperimental studies, [74][75][76][77][78][79][80][81][82][83][84][85][86][87] while the remaining 9 were cluster randomised trials.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%